2020
DOI: 10.1080/00365521.2020.1770851
|View full text |Cite
|
Sign up to set email alerts
|

Factors involved in endoscopists’ choice for prophylactic clipping after colorectal endoscopic mucosal resection: a discrete choice experiment

Abstract: Background: Delayed bleeding (DB) occurs in $10% after colorectal EMR. Prophylactic clipping (PC) was reported to significantly decrease DB-rate in proximal lesions !2 cm. Objective: Our aim was to determine which predefined variables contribute to using PC in clinical practice. Methods: We performed an international discrete choice experiment (DCE) among $500 endoscopists. Relevant variables for PC use were selected by EMR experts: previous DB, anticoagulants, polyp size, morphology, location, intraprocedural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This finding is in contrast with daily clinical practice, with studies showing that the routine use of antithrombotics is the most important decision factor for endoscopists to use prophylactic clips. 18,36 Our study has some limitations. Not all authors that were approached shared patient data for varying reasons.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This finding is in contrast with daily clinical practice, with studies showing that the routine use of antithrombotics is the most important decision factor for endoscopists to use prophylactic clips. 18,36 Our study has some limitations. Not all authors that were approached shared patient data for varying reasons.…”
Section: Discussionmentioning
confidence: 90%
“…9,10,13 Nonetheless, it has been reported that the use of antithrombotics is the most important decision factor for endoscopists to use prophylactic clips in daily clinical practice. 18,19 To reach consensus about the patient groups that may benefit from prophylactic clipping, a detailed and robust analysis of the available data is important. Although a meta-analysis of aggregated data is limited by reporting issues and sample size of the individual studies, an individual patient data meta-analysis (IPDMA) may offer a solution by collecting raw data from the included studies and combining these into 1 large dataset.…”
Section: Q7mentioning
confidence: 99%
“…Regarding accessories, in clinical practice prophylactic clipping of polyp resection defects does not always adhere to current recommendations and its overuse should be discouraged [69]. In this sense, determining the average need of accessories per procedure and periodically revisiting the number of accessories used could help to reduce waste and gain efficiency.…”
Section: Less Invasive Test Indication Endorsed By Guidelines Researchmentioning
confidence: 99%